2009
DOI: 10.1177/0193945909343594
|View full text |Cite
|
Sign up to set email alerts
|

La Mancha Negra: Substance Abuse, Violence, and Sexual Risks Among Hispanic Males

Abstract: Hispanics are disproportionately affected by substance abuse, intimate partner violence, and HIV. Although the relationship between these conditions has been documented in the literature, few studies have explored the intersection of these health problems and their culture-related risk factors in an integrative manner. The purpose of this study is to explore the experiences that Hispanic heterosexual males in South Florida have with substance abuse, violence, and risky sexual behaviors. Three focus groups with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 25 publications
3
56
1
2
Order By: Relevance
“…These results confirm previous research findings (e.g., Fernández-Montalvo et al, 2011;Yépez, 2014). In this regard, some studies have showed that youth, low educational levels, lower income levels, unemployment and lack of opportunities related to belonging to an ethnic minority are associated with higher risk of IPV (González-Guarda, Ortega, Vásquez, & De Santis, 2010;Jasinski, 2001;Vives-Cases et al, 2014;West, 2005). No difference in self-esteem and impulsivity were found between Latin American immigrants and Spanish batterers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results confirm previous research findings (e.g., Fernández-Montalvo et al, 2011;Yépez, 2014). In this regard, some studies have showed that youth, low educational levels, lower income levels, unemployment and lack of opportunities related to belonging to an ethnic minority are associated with higher risk of IPV (González-Guarda, Ortega, Vásquez, & De Santis, 2010;Jasinski, 2001;Vives-Cases et al, 2014;West, 2005). No difference in self-esteem and impulsivity were found between Latin American immigrants and Spanish batterers.…”
Section: Discussionsupporting
confidence: 90%
“…Estos resultados coinciden con los obtenidos en estudios realizados con agresores inmigrantes de otras nacionalidades y en población inmigrante latinoamericana en general (e.g., Fernández-Montalvo et al, 2011;Yépez, 2014). En la misma línea, diversos estudios han mostrado que la juventud, los niveles educativos bajos, menores niveles de ingresos, el desempleo y la falta de oportunidades relacionadas con la pertenencia a una minoría étnica se asocian a un mayor riesgo de violencia contra la pareja (González-Guarda, Ortega, Vásquez y De Santis, 2010;Jasinski, 2001;Vives-Cases et al, 2014;West, 2005). Además, no se encontraron diferencias significativas en autoestima e impulsividad entre los grupos.…”
Section: Discussionunclassified
“…Participants who were older were less likely to report substance abuse in the past three months (AOR = 0.93, 95% CI = 0.89, 0.97) and participants reporting increased depressive symptoms were more likely to report substance abuse (AOR = 1.05, 95% CI = 1.01, 1.09). The findings from this study supports previous research findings linking depressive symptoms with substance use/abuse in Hispanic men (Gonzalez-Guarda, Florom-Smith, & Thomas, 2011;Gonzalez-Guarda et al, 2010;Maisto, Palfai, Vanable, Heath, & Woolf-King, 2012). Additionally, this contradicts this study's proposed hypothesis that increased age in middle age HMSM may increase risk for depression; however, this study was not exclusively middle age HMSM.…”
Section: Depressive Symptoms In Hispanic Men Who Have Sex With Men (Hsupporting
confidence: 90%
“…As a population, HMSM continue to experience health disparities and issues regarding acculturation, substance use and high risk sexual practices that ultimately increase their risk for HIV infection (Gonzalez-Guarda, Ortega, Vazquez, & De Santis, 2010). Because Hispanics experience a disproportionate burden of HIV infection and 30.7% lacked health insurance, HIV infection is a serious threat to the health of the Hispanic community (CDC, 2013).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Because literature is nonexistent that compares the substance use behaviors among these two groups of Hispanic men, it is difficult to make comparative interpretations of findings from this sample. Previous research with both Hispanic MSM and Hispanic heterosexual men has identified factors such as acculturation, depression, low self-esteem, and other mental health conditions that are related and may contribute to substance use and abuse (Gonzalez-Guarda, Florom-Smith, & Thomas, 2011; Gonzalez-Guarda, Ortega, Vazquez, & DeSantis, 2010). More research is needed to explore how these factors influence substance use when substance use behaviors are compared by sexual orientation among Hispanic men.…”
Section: Discussionmentioning
confidence: 99%